2018
DOI: 10.3390/ijms19113668
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Mechanism of Salt Excluders under Saline Conditions and Its Applications

Abstract: Global soil salinization is increasingly a serious threat to agriculture worldwide. Therefore, it is imperative to improve crop salt tolerance as a means of adaptation to saline habitats. Some halophytes and most monocotyledonous crops are salt-excluders. Understanding the regulatory mechanisms of salt exclusion at the molecular level in salt-exclusion plants is critical for improving the salt tolerance of monocotyledonous crops such as maize, wheat, rice, and sorghum. In this review, we summarize recent resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 84 publications
(109 reference statements)
2
73
1
Order By: Relevance
“…Salt stress is a serious problem that limits crop production worldwide (Munns and Tester, 2008;Chen et al, 2018). Many C2H2-type TFs act as transcriptional activators or repressors to regulate plant responses to salt stress (Han et al, 2014).…”
Section: Roles In Salt Stressmentioning
confidence: 99%
“…Salt stress is a serious problem that limits crop production worldwide (Munns and Tester, 2008;Chen et al, 2018). Many C2H2-type TFs act as transcriptional activators or repressors to regulate plant responses to salt stress (Han et al, 2014).…”
Section: Roles In Salt Stressmentioning
confidence: 99%
“…Plants are capable of adjusting their water balance in response to salt stress. Plants adapt to osmotic stress mainly by reducing transpiration and accumulating osmotic adjustment substances (Chen M. et al, 2018). It has been reported that sorghum accumulated proline and soluble carbohydrates after NaCl treatment for 20 days (Heidari, 2009).…”
Section: Osmotic Stressmentioning
confidence: 99%
“…Correspondingly, plants have evolved some defensive mechanisms such as root Na + exclusion, osmolyte synthesis and antioxidant induction. These defensive mechanisms generally work more effectively in halophytes, and additionally, some special defensive behaviors exist in halophytes for their survival in saline land, such as salt secretion by glands and salt accumulation in vacuoles as osmolytes [8][9][10][11][12]. Plant survival and growth largely depend on photosynthesis.…”
Section: Introductionmentioning
confidence: 99%